2021
DOI: 10.1080/23273798.2021.1922726
|View full text |Cite
|
Sign up to set email alerts
|

Independent effects of collocation strength and contextual predictability on eye movements in reading

Abstract: Collocations are commonly co-occurring word pairs, such as "black coffee". Previous research has demonstrated a processing advantage for collocations compared to novel phrases, suggesting that readers are sensitive to the frequency that words co-occur in phrases. However, a further question concerns whether this processing advantage for collocations occurs independently from effects of contextual predictability. We examined this issue in an eye movement experiment using adjectivenoun pairs that are strong coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 36 publications
(56 reference statements)
6
12
1
Order By: Relevance
“…Their proficiency level and self-assessment scores indicated that participants were intermediate L2 learners. It was not possible to use an a priori power analysis to estimate the sample size given the lack of closely comparable studies (see Li et al, 2021 , for discussion). Accordingly, we used sensitivity analysis to estimate the smallest effect size that might be detected for interaction between collocation strength and context ( Lakens, 2021 ), employing software created by Westfall.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Their proficiency level and self-assessment scores indicated that participants were intermediate L2 learners. It was not possible to use an a priori power analysis to estimate the sample size given the lack of closely comparable studies (see Li et al, 2021 , for discussion). Accordingly, we used sensitivity analysis to estimate the smallest effect size that might be detected for interaction between collocation strength and context ( Lakens, 2021 ), employing software created by Westfall.…”
Section: Methodsmentioning
confidence: 99%
“…Stimuli were forty pairs of adjective-noun phrases obtained from the British National Corpus ( Burnage and Dunlop, 1992 ) used as stimuli in Li et al (2021) experiment. Each pair combined a different adjective with the same noun (e.g., black coffee and bitter coffee).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations